Spillover and Competition Effects: Evidence from the Sub-Saharan African Banking Sector - Birte Pohl (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
This paper examines the efficiency effects of foreign bank entry on domestic banks in sub-Saharan Africa during the period 1999-2006. Using a recently compiled dataset on foreign bank presence, the competition and spillover effects of North-South, regional and nonregional South-South banks are distinguished. The results show that the competitive pressure on domestic banks' net interest margins emanates only from regional South-South banks. There is evidence of spillover effects from North-South and regional South-South banks on domestic banks. As domestic banks invest in foreign technologies, their overhead costs increase in the short-run. Non-regional South-South banks seem to have little effect on the efficiency of domestic banks.
Keywords: F21; F23; F36; 330; Sub-Saharan Africa; efficiency; South-South banks; spillover